ANALISIS PENGARUH KUALITAS LAYANAN JASA PADA PT. BANK TABUNGAN NEGARA (PERSERO) CABANG SAMARINDA - Novia, Puput Rema (EKONOMIA, 2012)
Cooperative Samarinda civil town hall is one of the social enterprices. These cooperative engaged in saving and loans and services in the financial statetment of the cooperative must be in accordance with the statetment of financial accounting standart No.27 as for the purpose of writing this report to know the difference calculation of net income of cooperative civil courthouse with a statement of financial accounting standart No.27 of 2009 on financial accounting.